Enhancing Play Script Writing Skills with Canva Media and KIK-IRMA Learning Model: A Study on Indonesian Literature Students - Irma Suryani; Julisah Izar; Priyanto Priyanto (STAI Hubbulwathan Duri, 2025)
This study investigates the use of Canva media combined with the KIK-IRMA learning model in teaching play script writing to students in the Indonesian Literature Study Program at FKIP, Universitas Jambi. The objective was to determine the effectiveness of this integrated approach in enhancing students’ writing skills. A mixed-methods approach was employed, incorporating both qualitative and quantitative data. Qualitative data were collected through classroom observations, while quantitative data were gathered through pretests and posttests. The research instruments included observation sheets and test materials. Qualitative analysis was conducted descriptively and argumentatively, referencing relevant theories. Quantitative analysis was used to evaluate the validity, practicality, and effectiveness of the learning model. The study found a significant improvement in students’ performance. The average pretest score was 57.72, increasing to 80.59 in the posttest. The normalized gain score (N-gain) indicated a moderate level of effectiveness. Prior to implementation, students struggled with play script writing. However, after applying Canva and the KIK-IRMA model, both the learning process and outcomes showed notable improvement. The findings demonstrate that combining Canva media with the KIK-IRMA model can address student difficulties in play script writing. This integrated approach fosters student engagement and supports learning goals effectively. The implementation of Canva media and the KIK-IRMA learning model in play script writing was systematic and yielded moderately effective results in the Indonesian Literature Study Program at FKIP Universitas Jambi.